Transtornos reprodutivos causados por agentes infecciosos em animais de canis comerciais da microrregião de Ribeirão Preto, estado de São Paulo - Tavares, Denise Claudia [UNESP] (2015)
The commercial kennel breeding is an important economic activity in Brazil and has increased, in media, on 20% per year. The breeding has given importance to concern in the improvement of breeds, modernization and use of reproductive biotechnologies. Nevertheless, the reproductive performance is overlooked in breeding of dogs, though of significant losses due of reproductive disorders caused by inadequate sanitary management, culminating in abortions and neonatal/pup losses. Thus, the aim of this study was investigated the infectious causes of abortion and neonatal/pup deaths in commercial kennels. Blood samples from 400 dogs with an average age 29.1 ± 8.9 months were collected from kennels located in the microregion of Ribeirão Preto, SP, for serological and molecular. The data regarding to health and reproductive management were collected by a questionnaire. The studied was based on prevalence of Brucella canis (imunochromatography), Toxoplasma gondii (indirect immunofluorescence reaction), Neospora caninum (indirect immunofluorescence), Leptospira ssp (microscopic soroagglutination), canine Herpesvirus (PCR), Ehrlichia canis e Ehrlichia sp (PCR). The statistical analysis was descriptive, and we used the simple and multiple linear regressions to verify the interaction between dependent variables (abortion and neonatal/pup deaths) and percent positive cases. Canine population studied consisted of 108 males (27,0%, IC95%: 22,65-31,35) and 292 females (73,0%; IC95%: 68,65-77,35). The prevalence of diseases studied was B. canis (15,0%; IC95%: 11,50-18,50), T. gondii (17,3%; IC95%: 13,55-20,95), N. caninum (30,50%; IC95%: 26,19-35,18), Leptospira spp (34%; IC95%: 29,53-38,77), Ehrlichia sp (4,5%; IC95%: 2,87-7,00) and E. canis (15,5%; IC95%: 11,95-19,05), There was no positive case of canine herpesvirus. When the variable abortion was avaliable we can got one association with T. gondii (p = 0,004260) and B. canis (p = 0,0000012). When ...